The roles of homologous recombination and the immune system in the genomic evolution of cancer - Nandi, B (J Transl Sci, 2018)
A variety of factors, whether extracellular (mutagens/carcinogens and viruses in the environment, chronic inflammation and radiation associated with the environment and/or electronic devices/machines) and/or intracellular (oxidative metabolites of food, oxidative stress due to inflammation, acid production, replication stress, DNA replication/repair errors, and certain hormones, cytokines, growth factors), pose a constant threat to the genomic integrity of a living cell. However, in the normal cellular environment multiple biological pathways including DNA repair, cell cycle, apoptosis and the immune system work in a precise, regulated (tightly controlled), timely and concerted manner to ensure genomic integrity, stability and proper functioning of a cell. If damage to DNA takes place, it is efficiently and accurately repaired by the DNA repair systems. Homologous recombination (HR) which utilizes either a homologous chromosome (in G1 phase) or a sister chromatid (in G2) as a template to repair the damage, is known to be the most precise repair system. HR in G2 which utilizes a sister chromatid as a template is also called an error free repair system. If DNA damage in a cell is so extensive that it overwhelms the repair system/s, the cell is eliminated by apoptosis. Thus, multiple pathways ensure that genome of a cell is intact and stable. However, constant exposure to DNA damage and/or dysregulation of DNA repair mechanism/s poses a risk of mutation and cancer. Oncogenesis, which seems to be a multistep process, is associated with acquisition of a number of genomic changes that enable a normal cell to progress from benign to malignant transformation. Transformed/cancer cells are recognized and killed by the immune system. However, the ongoing acquisition of new genomic changes enables cancer cells to survive/escape immune attack, evolve into a more aggressive phenotype, and eventually develop resistance to therapy. Although DNA repair (especially the HR) and the immune system play unique roles in preserving genomic integrity of a cell, they can also contribute to DNA damage, genomic instability and oncogenesis. The purpose of this article is to highlight the roles of DNA repair (especially HR) and the immune system in genomic evolution, with special focus on gastrointestinal cancer.